2020
DOI: 10.1007/s13197-020-04348-y
|View full text |Cite
|
Sign up to set email alerts
|

Meat quality attributes and oxidation stability of loin chops from finishing gilts and cull sows

Abstract: The objective of this study was to compare the meat quality attributes, color stability, and lipid oxidation of loin chops from finishing gilts and cull sows in a threeway crossbreeding system: landrace 9 large white 9 duroc finishing gilts (n = 20) and landrace 9 large white sows (n = 20). No significant differences in pH, proximate composition, or total collagen content were found between the two pig groups. However, sow loin chops exhibited different quality characteristics for color, cooking loss, protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…There was no significant difference in these attributes between the muscle groups of cull sows and commercial pigs (p>0.05). This corresponds with the results of Song et al (2020a) . In contrast, Hoa et al (2020) and Kim and Kim (2018) reported significant differences in the crude protein and moisture content of a similar comparison.…”
Section: Resultssupporting
confidence: 92%
“…There was no significant difference in these attributes between the muscle groups of cull sows and commercial pigs (p>0.05). This corresponds with the results of Song et al (2020a) . In contrast, Hoa et al (2020) and Kim and Kim (2018) reported significant differences in the crude protein and moisture content of a similar comparison.…”
Section: Resultssupporting
confidence: 92%
“…No significant differences (p > 0.05) were found between the RP groups for the other characteristics studied. Previous studies reported an average backfat thickness of 27.2 mm [37], 29.4 mm [38], and 21.1 mm [5] for different carcass weight classes of culled sows, i.e., 175-199.9 kg in the former two studies and 183.5 kg in the latter, which were more similar to the fat thickness of the present study. Song et al (2020) [5] argued that differences in fat thickness may be due to fat loss during pregnancy and lactation, differences in genotype, or production system.…”
Section: Carcass Compositionsupporting
confidence: 86%
“…Therefore, effective culling management and further valuable use of culled sows are considered critical factors for improving profitability in commercial pig farms [5]. Globally, sow culling rates can vary significantly between herds, ranging from 26% to 70% [4].…”
Section: Introductionmentioning
confidence: 99%
“…Females at the end of their productive life or with unfit performance are culled from the farm and sent to slaughter. This is a crucial decision for the farm's efficiency, as it directly affects its economic sustainability [1]. The most frequent reasons for culling include reproductive failure, lameness, aging, and reduced health, which affect the sow's reproductivity and longevity [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Both sow carcasses and meat are poorly valued in retail cuts due to their undesirable aromas and flavors [12], sometimes addressed as 'sow taint' [13]. As such, this meat is mostly used in processed meat products, such as fresh pork sausages and meatballs [1,12,14]. The causes of boar taint in sows have not been identified, and there are no studies to date on the origin and composition of these atypical aromas and flavors in sow meat.…”
Section: Introductionmentioning
confidence: 99%